תשובה:
הערך הוא #-2#
הסבר:
תן # x = (2 + sqrt5) ^ (1/3) + (2-sqrt5) ^ (1/3) # לאחר מכן
# (3) = {(2 + sqrt5) ^ (1/3) + (2-sqrt5) ^ (1/3)} ^ 3 #
תזכורת:
# (a + b) ^ 3 = a + 3 + b ^ 3 + 3ab (a + b), a ^ 2-b ^ 2 = (a + b) (a-b) #
ולתת # a = (2 + sqrt5), b = (2-sqrt5):. ab = 4-5 = -1 #
# (: 3 + 1/3) 3 (2 + sqrt5) (2-sqrt5) (2 + sqrt5) (2 + sqrt5) (2 + sqrt5) + 2-sqrt5) #
או # 2 + 3 + 2 + ביטול (sqrt5) + 2-ביטול (sqrt5) +3 (4-5) (2 + לבטל (sqrt5) + 2 ביטול (sqrt5) # #
או # x ^ 3 = 4 + 3 (-1) (4) או x ^ 3 = 4 -12 או x ^ 3 = -8 # או
#x = (-8) ^ (1/3) = -2 #. הערך הוא #-2# Ans